Does anaerobic speed reserve influence post-activation performance enhancement in endurance runners? - Rosso, S. D.; Varela-Sanz, A.; Tuimil, J. L.; Boullosa, D. (Applied Physiology, Nutrition, and Metabolism, 2024)
We investigated the influence of anaerobic speed reserve (ASR) on post-activation performance enhancement (PAPE). Twenty-two endurance runners and triathletes were evaluated for maximum sprinting speed (MSS) and countermovement jump (CMJ) before (non-fatigued) and after (fatigued) an incremental running test. They were allocated in LASR (low-ASR) and HASR (high-ASR) groups for comparisons between conditions. HASR showed greater CMJ and MSS (both p = 0.005) performances, with enhanced CMJ in fatigued condition (p = 0.008). Significant correlations were found between ASR, CMJ, and MSS in both conditions (p = 0.01) for the entire sample, and between deltaCMJ and deltaMSS (p = 0.001) in LASR. Our results show that ASR profile influences PAPE.